Professionalism of Employee Work at the Public Works and Spatial Planning Office of Gowa Regency - Risma Niswaty; Muhammad Gilang Renaldy; Sitti Hardiyanti Arhas (International Journal of Administration and Education (IJAE), 2024)
In a digital era like this that has a big impact on implementing work professionalism, it is necessary to organize apparatus resources that not only understand work but are also able to use digital well. This study aims to find out the picture of the professionalism of employees in the PUPR Secretariat of Gowa Regency. This research is descriptive by using qualitative methods and approaches to find out the picture of the professionalism of the work of employees in the PUPR secretariat of Gowa Regency. The number of informants in this study is 3 people, namely 1 Head of Service, and 2 from the Head of Sub-Division. The data collection techniques used are observation methods, interview methods, and documentation methods. The data analysis technique in this study uses data collection techniques, condensation, data presentation, and conclusion drawing funds. The results of this study show that the professionalism of employees at the Public Works and Spatial Planning Office of Gowa Regency is in the "Good" category, this can be seen in each dimension, namely indicators of employee skills, it is good to see from employees who have skills that help their work process such as communication skills, governance skills in working creatively and innovatively. Competency indicators are good as evidenced by the existence of training on knowledge in doing work and competence in running software such as Microsoft Word and Excel. The indicator of employee loyalty is good, as evidenced by the cooperation between employees and leaders is good without any distinction so that employees are loyal to their agencies.